Molecular Design of Blue Phosphorescent Host Materials for Phenylimidazole‐Type Blue Triplet Emitters to Extend Operational Lifetime. Issue 12 (27th March 2018) - Byeon, Sung Yong; Han, Si Hyun; Lee, Jun Yeob
Abstract: Herein, a molecular design to improve the quantum efficiency and lifetime of blue phosphorescent devices by managing the lowest unoccupied molecular orbital is developed. This is accomplished by introducing a strong electron‐withdrawing cyano (CN) moiety into the chemical structure, which is made up of carbazolylcarbazole and dibenzothiophene. The CN moiety is selectively introduced into the dibenzothiophene unit or carbazolylcarbazole unit to investigate the effect of the CN position on the device performance of blue phosphorescent organic light‐emitting diodes (OLEDs). It is demonstrated that substituting CN into dibenzothiophene effectively facilitates electron injection and enhances the quantum efficiency of the blue OLEDs. A high external quantum efficiency of 26.8% is achieved in the blue phosphorescent devices using an imidazole ligand‐derived Ir emitter based on the molecular design to modify dibenzothiophene with the CN moiety. This also extends the lifetime of the blue phosphorescent device doped with the CN‐modified, imidazole ligand‐derived Ir emitter. Abstract : New host materials with a cyano substituent for blue phosphorescent organic light‐emitting diodes are developed to exhibit high efficiency and device operational lifetime based on the phenylimidazole‐type blue triplet emitters.